Dog stories in basic vocabulary - Dolch, Edward W. (Edward William), 1889-1961 (Basic vocabulary series., 1954)
Dog stories, based on newspaper or other news reports, about a sheep dog, fire house mascots, children's pets, and others, many of which performed heroic deeds.